Relationship between ecological quality and ecosystem services in a red soil hilly watershed in southern China - Qing Zhu (Elsevier, 2021)
Ecological quality (EQ) is the foundation of all ecosystem services (ESs) and is critical for the improvement of human welfare. To clarify the link between ecosystems and human well-being, the present study investigated the relationship between EQ and ESs in the Pingjiang watershed in a red soil hilly region (southern China) in 2016. The remote sensing ecological index (RSEI) and the ecosystem service index (ESI), respectively, were used to characterize EQ and four major ESs, i.e., water yield (WY), soil conservation (SC), carbon storage (CS), and food supply (FS). The relationship between EQ and ESs was explored at the sub-watershed scale. Results showed that the EQ of the Pingjiang watershed decreased from the surroundings to the central south. The spatial distributions of SC, CS, and ESI were similar to the EQ distribution, while FS exhibited an opposite trend. The spatial aggregation patterns of RSEI and ESI were somewhat similar, with a Spearman’s correlation coefficient (r) of 0.690 (P < 0.01), indicating that the overall coordination of EQ and ESs was high. In addition to RSEI, the normalized difference vegetation index, wetness component, and the normalized differential build-up and bare soil index all had the highest correlations with SC (|r| = 0.606–0.890, P < 0.01) among the four ESs. Only the normalized difference vegetation index was significantly correlated with WY (r = 0.274, P < 0.01), while land surface temperature had the greatest correlation with CS (r = −0.691, P < 0.01). This study enhances our understanding of the spatial and quantitative relationships between EQ and ESs in the Pingjiang watershed, and could facilitate decision-making for local governments in pursuit of sustainable development in similar watersheds.